Determinan Tingkat Pengetahuan Tentang Risiko Pemakaian Headset Dengan Sikap Penggunaan Headset Pada Mahasiswa - Ida Listiana; Mochamad Hasan; Wida Rosmayati (Edu Masda Journal, 2021)
Headset refers to a pair of small loudspeakers that are worn on or around the head above the user's ear. World Health Organization (WHO) stated in 2019 that nearly 50% or 1.1 billion adolescents and young adults (12 to 35 years old) are at risk of hearing loss due to loud and long exposure to sound, including music they listen to through personal audio devices and the 2018 WHO projection shows that if no action is taken, there will be 630 million people living with hearing loss by 2030 and this number will continue to grow or 1 in 10 will experience hearing loss. The objective of this research is to determine a correlation between the students understanding of the headset usage risk and their attitudes of using headset at semester IV nursing students of STIKes Widya Dharma Husada Tangerang. The result of this research based on the data collected from the students showed that 21 students with well understanding of the headset usage risk have shown positive attitudes (32.3%). Meanwhile, 44 (67,7%) students with well understanding of the headset usage risk have shown negative attitudes. The result of the statistical calculation found that (p-value=0,421, α: 0,05). Therefore, it can conclude that there is no correlation between the students understanding of the headset usage risk and their attitudes of using headset. The suggestion based on this research is students should contribute by raising awareness about hearing loss and how to prevent it.